Green Human Resource Management Conceptual Approaches - Heny Desi Soviana; Veithzal Rivai Zainal; Lenny Christina Nawangsari (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Green human resource management is currently a trend that has begun to be implemented by several companies in the world. This indicates that the organization has begun to realize the importance of protecting the environment and applying these environmentally friendly practices in organizational performance. In this article, we will discuss the importance of green human resource management and its application in several dimensions. Green human resource management has many positive impacts on the organizations that implement it, one of which is to maintain business sustainability in the future and help organizations to maintain their competitive advantage in the midst of increasingly fierce business competition.